Asset markets contagion during the global financial crisis - Dimitris Kenourgios; Apostolos Christopoulos; Dimitrios Dimitriou (Multinational Finance Journal, 2013)
This study investigates the contagion effects of the 2007-2009 global financial crisis across multiple asset markets and different regions. It uses daily return data of six asset classes: stocks, bonds, commodities, shipping, foreign exchange and real estate. A robust analysis of financial contagion is provided by estimating and comparing asymmetric conditional correlations among asset markets during stable and turmoil periods. Results provide evidence on the existence of a correlated-information channel as a contagion mechanism among the U.S. stocks, real estate, commodities and emerging Brazilian bond index. The findings also support the decoupling of BRIC equity markets from the crisis, the diversification benefits of shipping and foreign exchange value of the U.S. dollar indices, and the existence of a flight to quality mechanism from risky U.S. assets to German bonds. This evidence has important implications for portfolio diversification strategies and the future work of policymakers.